Neuromagnetic correlates of voice pitch, vowel type, and speaker size in auditory cortex - Andermann, Martin; Vogt, Carolin; Winterstetter, Lisa; Rupp, André (NeuroImage, 2017)
Vowel recognition is largely immune to differences in speaker size despite the waveform differences associated with variation in speaker size. This has led to the suggestion that voice pitch and mean formant frequency (MFF) are extracted early in the hierarchy of hearing/speech processing and used to normalize the internal representation of vowel sounds. This paper presents a magnetoencephalographic (MEG) experiment designed to locate and compare neuromagnetic activity associated with voice pitch, MFF and vowel type in human auditory cortex. Sequences of six sustained vowels were used to contrast changes in the three components of vowel perception, and MEG responses to the changes were recorded from 25 participants. A staged procedure was employed to fit the MEG data with a source model having one bilateral pair of dipoles for each component of vowel perception. This dipole model showed that the activity associated with the three perceptual changes was functionally separable; the pitch source was located in Heschl's gyrus (bilaterally), while the vowel-type and formant-frequency sources were located (bilaterally) just behind Heschl's gyrus in planum temporale. The results confirm that vowel normalization begins in auditory cortex at an early point in the hierarchy of speech processing.